Fate of Asymptomatic Limb after Kissing Stents in Aortoiliac Occlusive Disease - Faheem Asem Ahmad; Martin Michael Hennessy; Alexander Fredrik Nath (Vascular Specialist International, 2022)
Purpose: Kissing stent angioplasty is an established endovascular treatment strategy for stenosis at the aortic bifurcation but not without its detractors. This study aimed to analyze the outcomes of kissing stents with regard to stent occlusion and complications in which an asymptomatic limb was treated. Materials and Methods : A total of 106 patients undergoing aortic bifurcation intervention from January 2015 to November 2020 were retrospectively reviewed. Only patients with at least one common iliac artery (CIA) ostium and undergoing bilateral CIA intervention were included in the study. Results : Patients were followed up for a median period of 26 months (interquartile range, 21-51 months). The TransAtlantic InterSociety Consensus (TASC)-II classification of lesions was as follows: A, 49%; B, 41%; C, 6%; and D, 5%. The treatment indication was limited to one side in 53% of patients. Technical and procedural success rates were 99% and 90%, respectively. Ischemic events in an asymptomatic limb occurred in 6% of cases, 3% due to late stent thrombosis >30 days, and 3% due to progression of downstream infrainguinal disease. Primary and secondary patency rates at 1, 3, and 5 years were 98%, 87%, and 85%, and 99%, 94%, and 94%, respectively. Periprocedural mortality developed in two patients with no amputation. Conclusion : Kissing stent deployment is a safe and effective strategy for the treatment of aortoiliac bifurcation disease. Unfavorable outcomes due to stenting in the asymptomatic iliac artery are very rare. Long-term surveillance is necessary due to the risk of late thrombosis or downstream disease progression.